Hirsutum l. турининг генетик салоҳиятидан фойдаланиш (FAN va JAMIYAT, 2023)
It is known that the cotton species G.hirsutum L. has forms such as "yucatanense", "latifolium", "morrilli", "richmondii" and "religiosum", which still have no clear place in taxonomy, caused ambiguous views of a number of taxonomists.This article presents the indicators of crossbreeding and fecundity of seeds of F hybrids obtained with the participation of subspecies and forms of cotton of the species G.hirsutum L.